Architectonic integrity of the polyphonic composition in the aspect of discourse-analysis - Belichenko, Nataliya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. The application of the concepts of architectonics and tectonics to a polyphonic work in order to reveal the basic differences in the logical structure of imitative and non-imitative polyphony is undertaken for the first time. Main objective of the study is a discourse analysis of the architectonic integrity of polyphonic work on the texture and thematic levels, in conditions of imitative and non-imitative polyphony. Methodology of the study. The application of the discursive approach makes it possible to investigate the ratio of the general tectonic archetypes of a musical work (as a kind of “linguistic” principles with their typical model) and a polyphonic musical work in its chronotypologically defined genre-compositional discursive practice (as a givenness of a musical speech). The projection of the concept of “arched” architectonics (V. Moskalenko) to a polyphonic structure makes it possible to differentiate it into simultaneous (“contrapuntal”), succession ("polyphonic") and resultant (synthesizing) varieties, in consideration of the multipartite and specific branching of the texture landscape of the polyphonic work by horizontal, vertical and diagonal simultaneously. Results and conclusions. The architectonic integrity of the polyphonic product is considered. It was revealed that the specificity of the polyphonic work, unlike the harmonious by its structure multivoiced music, is displayed primarily in its “texture landscape”. It found that in non-imitative polyphonic genres and forms (polymelodic and isorhythmic motets of the epochs Ars Antiqua and Ars Nova, contrapuntal or polythematical chorale arrangement on the cantus firmus, ostinato polyphonic variations, etc.), due to their many-tierity and gravitation toward compositional segmentation, the predominant effect of the simultaneous type of architectonic integrity is observed. In imitation polyphony (in particular, in ricercar or fugue), coordination “along the diagonal” causes the resulting type of architectonic thinking of the interpreter.